Pengaruh Social Media Marketing dan Variasi Produk terhadap Minat beli Konsumen pada CV. Blackpaint Printshop Pekanbaru - Amalia Ananda; Mashur Fadli (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the influence of social media marketing and product variety on consumers buying interest in CV. Blackpaint Printshop Pekanbaru. The study uses descriptive and quantitative statistical methods with the use of the Likert scale as a measurement. The population used is Blackpaint Printshop consumers. The sample of this study amounted to 100 respondents which were determined using accidental sampling techniques and using questionnaires in data collection techniques. The analysis of this study includes instrument tests, classical assumption tests and statistical tests processed with tools in the form of SPSS version 25. The results of this study show that social media marketing partially has a significant effect on consumer buying interest, product variation partially has a significant effect on consumer buying interest. Social media marketing and product variations simultaneously have a significant effect on consumer buying interest.